PEMBUNUHAN JURNALIS PALESTINA SHIREEN ABU AKLEH DALAM AKUN INSTAGRAM @HAJJAJ_CARTOONS (STUDI SEMIOTIKA PEIRCE) - Fadillah, Risalatul Fikriani; Chotimah, Dien Nur (Master of Communication Science Program, Universitas Diponegoro, 2024)
Caricatures are one of the effective ways to convey information, messages, and criticism because it considered more attractive. This study aims to identify the kind of sign present in the caricatures about the murder of Palestinian journalist Shireen Abu Akleh on the Instagram @hajjaj_cartoons account and describe its sign interpretation. This qualitative and descriptive research obtained the data sources from caricatures about the murder of Palestinian journalist Shireen Abu Akleh on the Instagram account @hajjaj_cartoons, and news stories relevant to this tragedy. These two data sources are collected by observation, screenshot, and take notes technique, and analyzed using Peirce's semiotic theory. The results are found: (1) There are 16 icons, 9 indexes, and 13 symbols; (2) the interpretations are about criticism and condemnation of the murder of Shireen Abu Akleh, Israel's act of not wanting to admit her actions that killed Shireen Abu Akleh, the actions of Israeli police attacking mourners during the funeral process of Shireen Abu Akleh, and the U.S. action declaring Israel innocent of the shooting of Shireen Abu Akleh.